ChemInform Abstract: 1, 1‐Diamino‐2‐nitroethylenes as Excellent Hydrogen Bond Donor Organocatalysts in the Michael Addition of Carbon‐Based Nucleophiles to β‐Nitrostyrenes. Issue 9 (4th March 2014) - da Silva, Rodrigo C.; da Silva, Gustavo P.; Sangi, Diego P.; de M. Pontes, Joao G.; Ferreira, Antonio G.; Correa, Arlene G.; Paixao, Marcio W.
Abstract The application of the title catalysts is presented in the Michael—addition of several functionalized nucleophiles to β—nitrostyrenes under mild conditions.